Principles of IVF laboratory practice - Montag, Markus; Morbeck, Dean (Dean E.) (Cambridge : Cambridge University Press, 2017)
Since the first successful human in-vitro fertilization (IVF) treatment in 1978, IVF has transformed from an experimental procedure to an established standard of care that is practised throughout the world. As the proven methodologies become more established, patients and practitioners expect higher live birth rates and excellent quality controls. This practical book covers every stage in the life of an IVF laboratory, from designing and planning the laboratory to training the embryologists and ongoing management and troubleshooting, providing step-by-step protocols for today's best practice. Complex and specialized procedures are described by experts in the respective fields using a common structure, which allows the reader to translate into standard operating procedures. The editors bring together a portfolio of techniques that will work in almost every laboratory, providing a foundation of good working practice for both new and experienced embryologists.
Title from publisher's bibliographic system (viewed on 25 May 2017).
Keywords: Fertilization in vitro, Human